English: Indonesia - Ika Agustina; Indri Astuti Handayani; Guritno Syahputra (JURNAL ILMIAH FARMASI SIMPLISIA, 2026)
Nutmeg shell waste in Indonesia can be processed into activated charcoal for cosmetic products. However, its formulation into liquid soap presents a technical constraint, as viscous surfactants risk coating the charcoal pores, thereby reducing adsorption capacity. This study aimed to formulate a liquid bath soap using nutmeg shell activated charcoal and evaluate its physical quality and adsorption capacity. The charcoal was prepared through thermal processing at 300°C and 500°C. This process yielded charcoal with a low ash content (2.68%) and a high iodine adsorption capacity (989.82 mg/g). The charcoal was subsequently incorporated into a liquid soap base at concentrations of 0% (Base), 5% (F1), and 10% (F2). The evaluation showed that the pH values of the soap (8.19–8.25) complied with the SNI 4085:2017 standard. Although the viscosity (5,680–6,400 mPas) remained above the maximum limit, the addition of charcoal significantly reduced the viscosity (p < 0.05). Furthermore, the adsorption capacity of the soap increased with higher charcoal concentrations (p < 0.05), reaching 380.67 mg/g for F1 and 609.14 mg/g for F2. In conclusion, the pores of the nutmeg shell activated charcoal remain open and functional within the liquid soap formulation, demonstrating its effectiveness as a deep-cleansing agent.